PENGARUH PERHATIAN KEPALA SEKOLAH DAN SIKAP AKHLAKUL KARIMAH GURU TERHADAP HASIL PENDIDIKAN KARAKTER SANTRI DI PONDOK MODERN DARUSSALAM GONTOR SE-JAWA TIMUR - Alivia Ismi (Jurnal Penelitian dan Penilaian Pendidikan, 2021)
Tesis ini bertujuan untuk mengetahui pengaruh perhatian kepala sekolah dan sikap akhlakul karimah guru terhadap hasil pendidikan karakter santri di pondok modern Darussalam Gontor se-Jawa Timur. Responden penelitian ini berjumlah 110 wali kelas di Pondok Modern Darussalam Gontor Putra 1 yang terletak di Ponorogo, Jawa Timur dan Pondok Modern Darussalam Gontor Putri 1 yang terletak di Ngawi, Jawa Timur. Pesantren ini terkenal dengan tingkat kedisipilinannya yang tinggi. Untuk menguji hipotesis, penelitian ini menggunakan metode kuantitatif inferensial dan dianalisis menggunakan teknik analisis jalur. Temuan dalam penelitian ini menghasilkan p21 = 0.425, thitung = 4.878 dan p-value = 0.000 < 0.05 yang berarti perhatian kepala sekolah berpengaruh langsung positif terhadap sikap akhlakul karimah guru. P31 = 0.243, thitung = 2.548 dan p-value = 0.006 < 0.05 yang berarti perhatian kepala sekolah berpengaruh langsung positif terhadap hasil pendidikan karakter santri. P32 = 0.291, thitung = 3.054 dan p-value = 0.0015 < 0.05 yang berarti sikap akhlakul karimah guru berpengaruh langsung positif terhadap hasil pendidikan karakter santri.   The results of the santri character education are educational outputs that are very much needed for the birth of a generation of intelligent characters. To achieve this goal, supporting factors that can maximize the results of character education are needed, including the attention of the principal, which is a form of awareness of the principal to observe the school community in accordance with its main functions and tasks, while the moral attitude of the teacher is the inherent commendable behavior in the educator who is embedded in his soul. So this thesis aims to determine the effect of the attention of the principal and the attitude of the teacher's morals to the results of the character education of students in Islamic Boarding School Darussalam Gontor in East Java. The respondents of this study were 110 homeroom teachers at Islamic Boarding School Darussalam Gontor for Boys 1 located in Ponorogo, East Java and Islamic Boarding School Darussalam Gontor for Girl 1 located in Ngawi, East Java. This boarding school is famous for its high level of discipline. To test the hypothesis, this study uses inferential quantitative methods and analyzed using path analysis techniques. The findings in this study resulted in p21 = 0.425, thitung= 4.878 and p-value = 0.000 <0.05, which means that the attention of the principal directly positively influences the moral attitude of teachers. P31 = 0.243, thitung = 2.548 and p-value = 0.006 <0.05, which means that the attention of the principal directly has a positive effect on the students' character education outcomes. P32 = 0.291, thitung = 3.054 and p-value = 0.0015 <0.05, which means that the moral attitude of the teacher's has a positive direct effect on the results of the students' character education. Thus, the results of this study are that there is a significant positive direct effect of the attention of the principal and the attitude of the teacher's morality towards the results of the character education of students.